Peran Air Susu Ibu untuk Mengurangi Derajat Ikterik pada Bayi Hiperbilirubinemia Fisiologis di Ruang Peristi RSI Sultan Agung Semarang - Septi Raisa Anjani; Tri Sakti Widyaningsih; Nana Rohana (STIKes Persada Husada Indonesia, 2023)
Hyperbilirubinemia is a clinical phenomenon that often occurs in newborns in the first week of life. In cases of hyperbilirubinemia in Malaysia 75%, 65% in America, and 51.47% in Indonesia. To reduce the amount of jaundice in babies, one way that can be done is to provide adequate breast milk. This type of research is quantitative, and descriptive observation with a cross sectional approach and using lember. Sampling technique with consecutive sampling. The population was 26 babies with physiological icteric in the PERISTI room of RSI Sultan Agung Semarang. The data obtained were analyzed using the Spearman rank test. The results of data analysis in the Peristi Room RSI Sultan Agung Semarang presented the MOST ASI frequency was 8-12 times a day with grade I physiological icteric. The statistical test results of the rank Spearman p value were 0.002 (<α = 0.05). The conclusion of this study is the relationship between the frequency of offering ASI with changes in the degree of physiological hyperbilirubinemia infants in the PERISTI Room of RSI Sultan Agung Semarang.